2015
DOI: 10.1016/j.bcp.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive factors in uteroplacental and systemic circulation link placental ischemia to generalized vascular dysfunction in hypertensive pregnancy and preeclampsia

Abstract: Preeclampsia is a pregnancy-associated disorder characterized by hypertension, and could lead to maternal and fetal morbidity and mortality; however, the pathophysiological mechanisms involved are unclear. Predisposing demographic, genetic and environmental risk factors could cause localized abnormalities in uteroplacental cytoactive factors such as integrins, matrix metalloproteinases, cytokines and major histocompatibility complex molecules leading to decreased vascular remodeling, uteroplacental vasoconstri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 223 publications
(273 reference statements)
3
127
0
4
Order By: Relevance
“…5) Treatment with the angiogenic factor PIGF or Preg placental extract, which we found to contain high PlGF and low sFlt-1 levels, increased MMP-2 and MMP-9 levels/activity in placenta and uterus of RUPP rats. The present observations with PlGF are consistent with our previous report that the angiogenic factor VEGF prevents the decreases in MMP-2 and MMP-9 in uterine, placental and aortic segments of RUPP rats [13], and other reports that PIGF promotes endothelial cell growth, vasculogenesis, and placental development [20]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5) Treatment with the angiogenic factor PIGF or Preg placental extract, which we found to contain high PlGF and low sFlt-1 levels, increased MMP-2 and MMP-9 levels/activity in placenta and uterus of RUPP rats. The present observations with PlGF are consistent with our previous report that the angiogenic factor VEGF prevents the decreases in MMP-2 and MMP-9 in uterine, placental and aortic segments of RUPP rats [13], and other reports that PIGF promotes endothelial cell growth, vasculogenesis, and placental development [20]. …”
Section: Discussionsupporting
confidence: 93%
“…sFlt-1 binds VEGF and PlGF in the circulation and inhibits their action on cell surface VEGFR-1 [34]. Circulating levels of sFlt-1 are 10-fold higher in pregnant than non-pregnant women, remain almost stable during the first and second trimester, then increase after the 36 th week of gestation and throughout the third trimester [20]. The circulating sFlt-1 levels and sFlt-1/PlGF ratio are much higher in preeclamptic than normal pregnant women from the second trimester onwards [25, 29, 33, 35, 36].…”
Section: Introductionmentioning
confidence: 99%
“…In support of this paradigm, studies have shown changes in the local and circulating levels of multiple factors including the pro-angiogenic vascular endothelial growth factor (VEGF) and placental growth factor (PlGF), the anti-angiogenic factors soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng), cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), hypoxia-inducible factor (HIF), reactive oxygen species (ROS) and angiotensin II (AngII) type 1 receptor (AT 1 R) agonistic autoantibodies (AT 1 -AA). These bioactive factors could in turn cause generalized EC dysfunction and HTN, renal glomerular endotheliosis and increased glomerular permeability leading to proteinuria, and cerebral endotheliosis leading to cerebral edema and seizures (Ali and Khalil, 2015; Shah and Khalil, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The hypoxia provokes the release of ROS, angiogenic and inflammatory cytokines, for example hypoxia-inducible factor-I while decreasing heme oxygenase-I (HO-I) and its metabolite carbon monoxide. [53] Changes in sFLT-I and PIGF precede clinical development of pre-eclampsia only. While changes in sEGN and PIGF precede delivery of small-for-gestational age neonate.…”
Section: The Immune-inflammatory Cascadementioning
confidence: 99%